Modelling and optimising hybrid process of wire arc additive manufacturing and high-pressure rolling - Gornyakov, Valeriy; Sun, Yongle; Ding, Jialuo; Williams, Stewart (Elsevier, 2022)
Hybrid process of wire arc additive manufacturing (WAAM) and high-pressure rolling can build large-scale components with low detrimental residual stress (RS) and distortion. We developed an efficient coupled process model for a steel wall to simulate the interaction between WAAM deposition and rolling. The predicted RS distributions and wall dimensions agree well with experimental results. Cyclic variation of longitudinal tensile RS occurs during WAAM deposition and inter-layer rolling in clamped condition. The influence depth of deposition and rolling is characterised by the number of the underlying layers that are plastically deformed after each process cycle. For the inter-layer rolling with a flat roller, the rolling has smaller influence depth than the deposition; consequently, the rolling does not eliminate but rather contains the regeneration of WAAM tensile RS after thermal cycles. Rolling with a slotted roller introduces more tensile plastic strain and thereby more effectively reduces WAAM tensile RS and unclamping distortion. Compared to the inter-layer rolling, stacked-four-layer rolling has larger influence depth and hence achieves similar RS mitigation efficacy with fewer rolling operations, while post-build rolling has lower efficacy due to insufficient penetration. Therefore, stacked-layers rolling with slotted roller is recommended for an optimal hybrid process of WAAM and rolling.
Keywords: Directed energy deposition; Cold working; Residual stress; Distortion; Numerical simulation